Toll-like receptors in the depressed and suicide brain - Pandey, Ghanshyam N.; Rizavi, Hooriyah S.; Ren, Xinguo; Bhaumik, Runa; Dwivedi, Yogesh (Journal of psychiatric research, 2014)
Abnormalities of the immune function in depression and suicide are based in part on the observation of increased levels of proinflammatory cytokines in the serum and postmortem brain of depressed and suicidal patients. We have examined if abnormalities of the innate immune receptors, known as Toll-like receptors (TLRs), in the brain are associated with depression and suicide, since the activation of these receptors results in production of cytokines. Of all the TLRs shown to be present in humans, TLR3 and TLR4 appear to be unique and important in brain function. We have determined the protein (by ELISA method) and mRNA expression (using qPCR) of TLR3 and TLR4 in the postmortem brain (dorsolateral prefrontal cortex [DLPFC]) of 22 depressed suicide victims, 11 non-depressed suicide victims, 12 depressed non-suicide subjects and 20 normal control subjects. We found that the mRNA expression of TLR3 and TLR4 was significantly increased in DLPFC of depressed suicide victims and in depressed non-suicide subjects, compared with controls. However, the protein expression of TLR3 and TLR4 was significantly increased in depressed suicide victims, but not in depressed non-suicide subjects compared with controls. The observed abnormalities of proinflammatory cytokines in the brain of suicide victims may be related to an abnormality of TLR3 and TLR4 over-expression. To our knowledge, this is the first study of TLRs in the brain of psychiatric subjects.